Ancistrobrevidines A-C and related naphthylisoquinoline alkaloids with cytotoxic activities against HeLa and pancreatic cancer cells, from the liana Ancistrocladus abbreviatus. (15th January 2021) - Fayez, Shaimaa; Cacciatore, Alessia; Sun, Sijia; Kim, Minjo; Aké Assi, Laurent; Feineis, Doris; Awale, Suresh; Bringmann, Gerhard
Graphical abstract: Highlights: Eight new axially chiral alkaloids were isolated from Ancistrocladus abbreviatus. The series comprises alkaloids of three different subclasses of naphthylisoquinolines. Two of them are the very first naphthylisoquinolines with a 3, 4-naphthoquinone portion. Ancistrobrevine C eliminates the tolerance of pancreatic cancer cells to nutrition starvation. Ancistrobrevine C is a potent antiausterity agent with antimetastatic activity. Abstract: From the leaves of Ancistrocladus abbreviatus (Ancistrocladaceae), six 5, 1′-coupled naphthyldihydroisoquinoline alkaloids were isolated, ancistrobrevidines A-C (5 –7 ), 5- epi -dioncophyllidine C2 (10 ), 6- O -methylhamatinine (8 ), and 6- O -methylancistectorine A3 (9 ); the two latter compounds were already known from related plants. Most strikingly, this series comprises alkaloids belonging to three different subclasses of naphthylisoquinolines. Ancistrobrevidine C (7 ) and the alkaloids 8 and 9, displaying the S -configuration at C-3 and an oxygen function at C-6, are three further representatives of the large subgroup of 5, 1′-coupled Ancistrocladaceae-type compounds found in nature. 5- epi -Dioncophyllidine C2 (10 ), lacking an oxygen function at C-6 and having the R -configuration at C-3, is only the third representative of a 5, 1′-linked Dioncophyllaceae-type naphthylisoquinoline. Likewise rare are 5, 1′-coupled hybrid-type alkaloids, which are 6-oxygenated and 3 R -configured. The ancistrobrevidines A (5 ) and B (6 ) are the only second and third examples of such 5, 1′-linked naphthylisoquinolines in Ancistrocladus species showing the landmarks of both, Ancistrocladaceae- and Dioncophyllaceae-type naphthylisoquinolines. In the roots of A. abbreviatus, two further unprecedented 5, 1′-coupled alkaloids were discovered, ancistrobreviquinones A (11 ) and B (12 ), consisting of a 3, 4-naphthoquinone portion coupled to a tetrahydroisoquinoline subunit. They are the very first quinoid naphthylisoquinolines possessing an ortho -diketone entity. Ancistrobrevidine C (7 ) exerted pronounced antiproliferative activities against HeLa cervical cancer cells and preferential cytotoxicity towards PANC-1 human pancreatic cancer cells under nutrient-deprived conditions following the antiausterity approach. Moreover, 7 suppressed the migration of PANC-1 cells and significantly inhibited colony formation under nutrient-rich conditions in a concentration-dependent manner, and induced dramatic alteration in cell morphology, leading to cell death.